(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2022)
The foliar and petiole anatomy and of the following 10 native woody species that occur in the seasonally deciduous dry forest of coastal Ecuador is described: Capparidastrum frondosum, C. petiolare, Colicodendron scabridum, Cynophalla ecuadorica and C. heterophylla (Capparaceae), Handroanthus chrysanthus, H. billgergii subsp. ampla and Tecoma castaneifolia (Bignoniaceae), Bursera graveolens (Burseraceae), and Bonellia sprucei (Primulaceae). The aim of this study is characterizing the fundamental tissues of leaf blades and petioles for each species and discussing the histological differences among those. The samples were fixed in FAA solution, subsequentlyfreehand cross-sections were made, those were rinsed in 5% sodium hypochlorite for the study of the epidermis and stained with safranin and methylene blue; plates were prepared for observation and analysis. The studied species exhibited the following traits: dorsiventral leaf blades, except for Handroanthus billbergii; hypostomatic leaves and drusen at the leaf mesophyll as in Bursera graveolens; trichomes simple, acicular, glandular, stellate and branched. The petiole of studied species reveal: a thick cuticle, abundant cortical parenchyma, collateral bundles arranged in the form of protostele or siphonostele, secretory channels and abundant drusen associated with the phloem.